The impact of corporate governance on marketing auditing: an analytical study of the opinions of a sample of employees in the Iraqi commercial banking sector - احمد كاظم بريس; شهد ابراهيم احمد (Iraqi Journal for Administrative Sciences, 2024)
This study aims to measure the impact of governance in the marketing audit in banks sector through the selection of a number of private commercial banks in Iraq and within the province of Karbala. Where the financial crises and cases of financial corruption and fraud experienced by many business organizations and financial institutions led to loss of confidence in the administrative systems and laws And monitoring and accounting, which made it necessary to clarify solutions and alternatives to regulate the relationship and raise the efficiency of control and management. In order to achieve this, the study relied on governance as an independent variable. Marketing audit was expressed as a dependent variable. The study reached a number of conclusions, the most important of which are the existence of significant relationship between the dimensions of governance, which means that banks can benefit from the governance in order to enhance the dimensions of the marketing audit.